Strategic Uncertainty, Equilibrium Selection, and Coordination Failure in Average Opinion Games - Van Huyck, J. B.; Battalio, R. C.; Beil, R. O. (Quarterly Journal of Economics, 1991)
Deductive equilibrium analysis often fails to provide a unique equilibrium solution in many situations of strategic interdependence. Consequently, a theory of equilibrium selection would be a useful complement to the theory of equilibrium points. A salient equilibrium selection principle would allow decision makers to implement a mutual best response outcome. This paper uses the experimental method to examine the salience of payoff-dominance, security, and historical precedents in related average opinion games. The systematic and, hence, predictable behavior observed in the experiments suggests that it should be possible to construct an accurate theory of equilibrium selection.